FREEDOM REFLECTED IN MAYA ANGELOU’S POEMS (A METAPHOR ANALYSIS) - Rapliyanto Polimengo (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This study focuses on the analysis of metaphor of six selected poems by Maya Angelou: A Freedom Fighter, Riot: 60's, The Calling of Names, Caged Bird, Harlem Hopscotch, and Equality. The research aims to explore how metaphors in these poems reflect the concept of freedom. Employing a descriptive qualitative approach combined with the method structuralism element of poem, the study analyzes metaphors based on Lakoff and Johnson’s (1980) theory of metaphor. The findings reveal that the metaphors in these poems depict struggles, oppression, and aspirations for freedom, particularly within the African-American community. Symbols such as the caged bird in Caged Bird and social chaos in Riot: 60's highlight profound emotions and collective experiences. This research contributes to the understanding of metaphor in poetry and serves as a reference for future studies on the representation of freedom in literary works.